Home Delivery Medicament Program: access, inactivity and cardiovascular risk - Roque da Silva Araújo; Edna Apparecida Moura Arcuri; Victor Cauê Lopes
ABSTRACT Objective: to verify causes of inactivity in the Home Delivery Medicament Program, as referred by users from a Primary Health Care Service in São Paulo, comparing them to the causes registered in the program and analyzing them in the theoretical model Concept of Access to Health. Methods: cross-sectional study, interviewing 111 inactive users; and documentary study in the program records. Results: half of the users did not know the condition of inactivity. Discrepancies were found between the user's and the program's information, observing different levels of agreement: Absence of physician and administrative staff member 0%; Transfer to other service 25%; Death 50%; Option to quit 50%; Address change 57% and Change in therapeutic schedule 80%. The users' feeling of accepting the program was observed. In the health access concept, inactivity can be explained in the information dimension, in the degree of asymmetry between the patient's and the health professional's knowledge, identified through the indicators: education, knowledge and information sources. Conclusions: due to the low education level, the user does not assimilate the information on the steps of the program flowchart, does not return for the assessment that guarantees its continuity. Consequently, (s)he stops receiving the medication and spends a long time without treatment, increasing the cardiovascular risk of hypertensive (92% of the sample), diabetic (44%) and dyslipidemic patients (31%).